2010
DOI: 10.2117/psysoc.2010.1
|View full text |Cite
|
Sign up to set email alerts
|

Re-Examination of the Effects of the "Finding Positive Meaning" Coping Strategy on Positive Affect and Health

Abstract: This study examined the effects of "finding positive meaning" coping on positive affect (PA) and health with methodological modifications to overcome limitations in Yamasaki et al. (2009). Participants in the intervention group (14 men and 15 women) reported the most stressful event during the past three days and its positive meaning, while those in the control group (16 men and 15 women) reported only the most stressful event. Both groups reported twice a week for nine successive weeks via e-mails. Four self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Studies reported (in descending order of frequency) on anxiety features (87 articles; 29.5%), affective symptoms (65 articles; 22.0%), other emotional and behavioral problems (62 articles; 21.0%), conduct problems (59 articles; 20.0%), general psychological distress (52 articles; 17.6%), alcohol use (42 articles; 14.2%), externalizing behaviors, (31 articles; 10.5%), tobacco use (32 articles; 10.8%), internalizing behaviors (25 articles; 8.5%), cannabis use (23 articles; 7.8%), ADHD features (21 articles; 7.1%), interpersonal violence (14 articles; 4.7%), eating-related problems (13 articles; 4.4%), consequences of alcohol use (12 articles; 4.1%), PTSD features (6 articles; 2.0%), sleep-related problems (6 articles; 2.0%), and impaired functioning (5 articles; 1.7%) (Supplemental Table 3, http://links.lww.com/HRP/A158). 44–133, 134–231, 232–332 …”
Section: Resultsmentioning
confidence: 99%
“…Studies reported (in descending order of frequency) on anxiety features (87 articles; 29.5%), affective symptoms (65 articles; 22.0%), other emotional and behavioral problems (62 articles; 21.0%), conduct problems (59 articles; 20.0%), general psychological distress (52 articles; 17.6%), alcohol use (42 articles; 14.2%), externalizing behaviors, (31 articles; 10.5%), tobacco use (32 articles; 10.8%), internalizing behaviors (25 articles; 8.5%), cannabis use (23 articles; 7.8%), ADHD features (21 articles; 7.1%), interpersonal violence (14 articles; 4.7%), eating-related problems (13 articles; 4.4%), consequences of alcohol use (12 articles; 4.1%), PTSD features (6 articles; 2.0%), sleep-related problems (6 articles; 2.0%), and impaired functioning (5 articles; 1.7%) (Supplemental Table 3, http://links.lww.com/HRP/A158). 44–133, 134–231, 232–332 …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, greater positive affect seems to be an important factor in resilience to and recovery from psychological stressors, including depressive and PTSD symptoms (Ong, Bergeman, Bisconti, & Wallace, 2006; Yamasaki, Uchida, & Katsuma, 2010). The NIMH Research Domain Criteria (RDoC) project has identified positive affect as an important area of functioning, and dysfunction of this system is considered to cut across diagnoses (Sanislow et al, 2010).…”
Section: Low Positive Affect and Psychopathologymentioning
confidence: 99%